Analysis of factors influencing parents’ willingness to accept the quadrivalent influenza vaccine for school-aged children in the Nanhai District, China - Pengbin Li; Zongyao Qiu; Wanling Feng; Hong Zeng; Weiming Chen; Zhipan Ke; Weiju Chen; Haiyun Lv; Guohan Luo; Ximing Huang (Human Vaccines & Immunotherapeutics, 2020)
Recently, China has attached great importance to promoting immunization, prompting the media, scholars, and public to focus on its coverage and efficacy. This study aimed to understand the factors influencing parental willingness to have their school-aged children vaccinated with quadrivalent influenza vaccines (QIVs). A cross-sectional study through face-to-face interviews was conducted between September and December 2018. Forty-four kindergartens and primary and junior high schools were randomly selected via stratified three-stage cluster sampling. Of 4,430 participants, 24.6% reported having heard of QIV and 24.2% reported having previously received information on QIV. Of these, 42.8% expressed willingness to obtain the QIV for their children. A junior college degree (adjusted odds ratio [aOR] = 1.447; 95% confidence interval [95% CI]: 1.202–1.742), higher influenza knowledge level (medium level, aOR = 1.150, 95% CI, 1.006–1.314; high level, aOR = 1.332, 95% CI, 1.045–1.697), and previous influenza information (aOR = 2.241; 95% CI, 1.604–3.130) were positively correlated with vaccination willingness. In contrast, no previous QIV-related information (aOR = 0.490; 95% CI, 0.418–0.575), no perceived susceptibility of children to influenza (aOR = 0.576; 95% CI, 0.489–0.680), fear of side effects (aOR = 0.599; 95% CI, 0.488–0.735), concern that vaccines need to be carefully administered (aOR = 0.728; 95% CI, 0.593–0.894), and mistrust of new vaccines (aOR = 0.730; 95% CI, 0.628–0.849) were pivotal barriers hindering parents from having their children vaccinated. This study provides baseline information for future immunization programs and delivery, with the ultimate goal of increasing vaccine uptake and minimizing school-wide influenza outbreaks.